Anonymi Monophysitae theosophia : an attempt at reconstruction - Beatrice, Pier Franco, 1948- (Vigiliae Christianae, Supplements, 2001)
The Theosophy , written by an anonymous Monophysite theologian in the early years of the sixth century CE, is a work in four books with a final world chronicle. Heir to a long apologetic tradition, it aims at demonstrating that there is a basic harmony between Christian faith and pagan theology. For this reason its author quotes at length numerous pagan prophecies of the Christian doctrines of the Trinity and the Incarnation. This volume proposes the first comprehensive critical edition of all the extant fragments of this work, in an attempt to reconstruct the general framework and to understand the inner logic of its composition. Thanks to this edition, which is bound to become the starting point for any future investigation, the Theosophy has now been put in circulation and made available for further research.